Analisis Kualitas Pelayanan Dan Kepercayaan Terhadap Kepuasan Konsumen Menggunakan Jasa JNE Express - Yunus, Muhammad; Tobing, Fitriani (Economics, Business and Management Science Journal, 2025)
This study aims to determine "Analysis of Service Quality and Trust on Consumer Satisfaction Using JNE EXPRESS Services (Case Study at PT. JNE EXPRESS Branch, Batang Kuis District)". This type of research is an associative and quantitative approach. The population in this study were consumers of PT. JNE EXPRESS as many as 149 customers using the slovin formula technique, so the number of samples in this study was 100 respondents taken from part of the population. Based on the results of the t test, it can be seen that the t count on the Service Quality and Trust variables is 3.191 and 5.831 t table of 1.659 with a probability of t, namely sig 0.05 on the Consumer Satisfaction variable. Based on the results of the F test, the F count value is 68.575 3.08 with Sig 0.000 0.05 indicating that Service Quality and Trust simultaneously have a positive and significant effect on the Consumer Satisfaction variable. The Adjusted R Square value obtained is 0.558 or 55.8% Consumer Satisfaction can be explained by Service Quality and Trust, the remaining 44.2% is influenced by other factors not explained in this study.